DEVELOPING MARKETING STRATEGY OF PT ANGKASA DWI UTAMA TO AMERICA - Felix Calvany Yonathan; Ijlal Setyoviyon; Annisa Alifa Khair; Muhammad Khusni Mubarrok; Najihah Binti Rosli (International Journal of Applied Business and International Management, 2018)
PT. Angkasa Dwi Utama, our company has two subsidiaries convinced backpackerjalanjalan.com and tour and travel of Putra Hadi. As we know traveling increasingly in demand by many people and society, but foreigners who are have travelling hobbies, our company can provide tours to several countries in Asia but our company is more concerned to travel in Indonesia. Indonesia has many beautiful spots around the country, but these spots are not published well to the other country. Because of that we use online media for promotion of our business and the hidden beautiful spots in Indonesia, we use website, facebook, twitter, etc. This company have good management systems and interesting tour and travel packages, but this company are not doing promotion well. This company is have great potential to be better, so our team try to help this company selling the product abroad specially USA. The recommended idea from our team is using promotion by social media. We use social media because that is the quickest way to promote it without going to the targeted country. Our team is try to cooperate with another travel agent abroad which is AmericaAsia.com Our team are very optimistic with this project to help the company being international travel agent. We are hoping that our recommended idea can help the company to get more and more travel agent partnership.